Pengaruh Perceived Value, Satisfaction dan Trust Berpengaruh terhadap Loyalty - Khasbara Rusli, Muh (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aim of this study is to assess the extent of the influence of sales promotion on consumer purchasing decisions at the All-in-One Store in Batam City. This research employs an analytical descriptive method with the entire store's consumers as the study population. Data collection utilizes a questionnaire distributed to 100 respondents. The findings indicate that sales promotion significantly impacts consumer purchasing decisions at the All-in-One Store in Batam City. This suggests that effective promotional efforts can enhance consumers' interest and purchasing decisions at the store. The implications of this study underscore the need for improved and more targeted sales promotion strategies to support sales growth and consumer satisfaction at the All-in-One Store.